The Status of the Acupuncture Mechanism Study Based on PET/PET-CT Technique: Design and Quality Control. (29th November 2019) - He, Zhaoxuan; Hou, Likai; Sun, Ruirui; Yin, Tao; Ma, Peihong; Chen, Li; Cheng, Shirui; Liu, Xiaoyan; Hong, Xiaojuan; Hou, Jian; Zeng, Fang
Abstract : PET/PET-CT is an important technique to investigate the central mechanism of acupuncture in vivo . This article collected original research papers with keywords of "Acupuncture, " "PET, " "PET/CT, " and "Positron emission tomography" in PubMed and CNKI databases from January 2003 to December 2018. As a result, a total of 43 articles were included. Based on the literature analyses, we found that (1) reasonable arrangement of the operation process and the choice of appropriate acupuncture intervention time is conducive to a better interpretation of acupuncture-PET/PET-CT mechanism and (2) the selection of participants, sample size, acupuncture intervention, and experimental conditions would affect study results. Therefore, effective quality control is an important way to ensure the repeatability of research results.